Similar Fecal Microbiota Signatures in Patients With Diarrhea-Predominant Irritable Bowel Syndrome and Patients With Depression - Liu, Yixuan; Zhang, Lu; Wang, Xiaoqi; Wang, Zhe; Zhang, Jingjing; Jiang, Ronghuan; Wang, Xiangqun; Wang, Kun; Liu, Zuojing; Xia, Zhiwei; Xu, Zhijie; Nie, Yong; et al. (Clinical gastroenterology and hepatology, 2016)
Patients with irritable bowel syndrome (IBS) often have psychiatric comorbidities. Alterations in the intestinal microbiota have been associated with IBS and depression, but it is not clear if there is a microbial relationship between these disorders. We studied the profiles of fecal microbiota samples from patients with IBS, depression, or comorbidities of IBS and depression; we determined the relationships among these profiles and clinical and pathophysiological features of these disorders. We used 454 pyrosequencing to analyze fecal microbiota samples from 100 subjects (40 with diarrhea-predominant IBS [IBS-D], 15 with depression, 25 with comorbidities of IBS and depression, and 20 healthy individuals [controls]), recruited at Peking University. Abdominal and psychological symptoms were evaluated with validated questionnaires. Visceral sensitivity was evaluated using a barostat. Colonic mucosal inflammation was assayed by immunohistochemical analyses of sigmoid tissue biopsy specimens. Fecal microbiota signatures were similar between patients with IBS-D and depression in that they were less diverse than samples from controls and had similar abundances of alterations. They were characterized by high proportions of Bacteroides (type I), Prevotella (type II), or nondominant microbiota (type III). Most patients with IBS-D or depression had type I or type II profiles (IBS-D had 85% type I and type II profiles, depression had 80% type I and type II profiles). Colon tissues from patients with type I or type II profiles had higher levels of inflammatory markers than colon tissues from patients with type III profiles. The level of colon inflammation correlated with the severity of IBS symptoms. Patients with IBS-D and depression have similar alterations in fecal microbiota; these might be related to the pathogenesis of these disorders. We identified 3 microbial profiles in patients that could indicate different subtypes of IBS and depression or be used as diagnostic biomarkers.